Adenopygus: a new genus and two new species of Luzarinae cricket of Brazilian Atlantic Forest (Orthoptera: Grylloidea) - Bolfarini, Marcio P. [UNESP]; Mello, Francisco de Assis Ganeo de [UNESP] (Magnolia Press, 2012)
The aim of the present work is to describe Adenopygus, a new genus with two species of luzarine phalangopsid crickets from the Atlantic Forest on the Mantiqueira fault escarpment of southeastern Brazil.
Keywords: Orthoptera; Grylloidea; Phalangopsidae; new taxa; description